V2 : a novel of World War II - Harris, Robert, 1957- (Alfred A. Knopf, 2020)
A World War II German rocket engineer under orders to launch V2 rockets at London from Occupied Holland and an actress-turned-English intelligence officer with a mission to neutralize the bombings land on opposite sides in a desperate hunt for a saboteur.